Peran Media Digital Berbasis AI dalam Pembelajaran Menulis Kreatif pada Siswa Kelas V UPT SD Negeri 005 Bonani Onan - Vera Ironita Christiani Sihombing; Gemala Widiyarti; Arina Situmorang; Grace Natalia; Nasrida Br Karo (Global Education Journal, 2026)
This study aimed to describe the role of Artificial Intelligence (AI)-based digital media in creative writing instruction for fifth-grade students at UPT SD Negeri 005 Bonani Onan. The study employed a qualitative approach using a descriptive research design. The research participants consisted of the fifth-grade teacher and fifth-grade students. Data were collected through observations, interviews, and documentation. The findings indicate that Artificial Intelligence (AI)-based digital media play an important role in supporting creative writing instruction at the elementary school level. The use of this media enhances the quality of the learning process, fosters students' creativity, and creates a more active, innovative, and meaningful learning experience. Therefore, AI-based digital media can be used as an alternative instructional medium to improve elementary school students' creative writing skills.